Fe-Pt-Ag-C-BASED SPUTTERING TARGET HAVING C PARTICLES DISPERSED THEREIN, AND METHOD FOR PRODUCING SAME - TAKAMI HIDEO; SATO ATSUSHI (2014)
An Fe-Pt-Ag-C-based sintered compact sputtering target having a composition represented by a formula (Fe100-X-PtX)100-Y-Z-AgY-CZ (wherein X represents a numerical value satisfying a formula 35 X 55; Y represents a numerical value satisfying a formula 0.5 Y 15; and Z represents a numerical value satisfying a formula 15 Z 55) when expressed in an atomic ratio, and having a relative density of 93% or more. A method for producing an Fe-Pt-Ag-C-based sintered compact sputtering target, characterized in that an Fe-Pt-C sintered compact is produced in advance, the sintered compact is pulverized to produce a pulverized powder, the pulverized powder is mixed with a Ag powder, and the resultant mixed powder is subject to sintering at a temperature lower than a melting point of Ag. An object of this invention is to provide a high-density sputtering target which enables the production of a magnetic thin film having a granular structure without the use of expensive co-sputtering equipment and which enables the reduction in the amount of particles generated during sputtering.